1996
DOI: 10.1111/j.1439-0329.1996.tb01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of clonal susceptibility, leaf age and inoculum density on infections by Melampsora larici‐populina races E1 and E3

Abstract: A study was conducted on the lnfiuence of clonal susceptibility, leaf age and inoculum density on the incubation and presporulation periods, and on the intensity of attack of Melampsora larici-populina races El and E3, under controfled conditions, on artificially inoculated poplar leaf discs. Both races were more virulent on susceptible clones and on 5-to 15-day-old leaves. On susceptible clones the intensity of attack increased progressively with the increase of inoculum density. Where there was complete cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Other studies reported differences in the susceptibility to rust of L. Avanzo. Artificially inoculated leaf discs of two strains of M. larici-populina showed that this clone was highly resistant to the E1 strain and highly susceptible to E3 (Giorcelli et al, 1996). Frey and Pinon (1997) also observed a wide range of reactions in L. Avanzo, ranging from susceptibility to resistance, depending on the isolate.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies reported differences in the susceptibility to rust of L. Avanzo. Artificially inoculated leaf discs of two strains of M. larici-populina showed that this clone was highly resistant to the E1 strain and highly susceptible to E3 (Giorcelli et al, 1996). Frey and Pinon (1997) also observed a wide range of reactions in L. Avanzo, ranging from susceptibility to resistance, depending on the isolate.…”
Section: Discussionmentioning
confidence: 95%
“…This is the first in-depth systematic report on the potential role of MoT seed infection in the short and long-distance dissemination of MoT. Transmission of seed-borne pathogens may depend on plant age ( Giorcelli et al, 1996 ), cultivar ( Roderick and Clifford, 1995 ), plant nutritional status ( Chowdhury et al, 2022 ), and plant growing conditions ( Nopsa and Pfender, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Table 3. Pathogenicity of E1-E4 of M. larici-populina from north-western Europe to some poplar clones (extracted from Pinon (1992) and Steeanckers (1994)) Host species/hybrid , 1996;Pei et al, 2003). In this study, disease was scored based on pustule area and inoculum density data according to the method described by Pei and Hunter (in press) using the following steps.…”
Section: Disease Assessmentmentioning
confidence: 99%